Is grip strength a good marker of physical performance among community-dwelling older people? - Stevens, P; Syddall, H; Patel, H; Martin, H; Cooper, C; Sayer, A (Springer-Verlag, 2012)
Introduction: There is increasing interest in physical performance as it relates to both the current and future health of older people. It is often characterised using the Short Physical Performance Battery including assessment of gait speed, chair rises and standing balance. However this battery of tests may not be feasible in all clinical settings and simpler measures may be required. As muscle strength is central to physical performance, we explored whether grip strength could be used as a marker of the Short Physical Performance Battery. Objective: To examine associations between grip strength and components of the Short Physical Performance Battery in older community dwelling men and women. Methods: Grip strength measurement and the Short Physical Performance Battery were completed in 349 men and 280 women aged 63-73 years taking part in the Hertfordshire Cohort Study (HCS). Relationships between grip strength and physical performance (6m time-dup-and-go [TUG], 3m walk, chair rises and standing balance times) were analysed using linear and logistic regression, without and with adjustment for age, anthropometry, lifestyle factors and co-morbidities. Results: Among men, a kilo increase in grip strength was associated with a 0.07s (second) decrease in 6m TUG, a 0.02s decrease in 3m walk time, and a 1% decrease in chair rises time (p<0.001 for all). Among women, a kilo increase in grip strength was associated with a 0.13s decrease in 6m TUG, a 0.03s decrease in 3m walk time, and a 1% decrease in chair rises time (p<0.001). Higher grip strength was associated with better balance among men (p=0.01) but not women (p=0.57). Adjustment for age, anthropometry, lifestyle and co-morbidities did not alter these results. Conclusions: Grip strength is a good marker of physical performance in this age group and may be more feasible than completing a short physical performance battery in some clinical settings. © 2012 Serdi and Springer-Verlag France.